Relationship between Pregnancy Depression and Sleep Quality of Pregnant Women in the Third Trimester at the Primary Health Care Wayabula - Alirce Norce Leang; Widia Shofa Ilmiah (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Sleep disturbances may be encountered by third-trimester gravid women owing to perceptual vicissitudes and physiological-psychological perturbations. Sleep caliber may be detrimentally impacted by depression precipitated by such gestational alterations. A quantitative correlational paradigm was harnessed in this inquiry to appraise the nexus betwixt gestational sleep quality and depressive symptomatology. The study cohort encompassed the entirety of pregnant women, from whom 41 were randomly conscripted. Kendall's tau-b correlational scrutiny yielded a coefficient of 0.649 and p-value of 0.000 (<0.05), evincing a robust, statistically salient association between prenatal sleep eminence and depression. Ergo, diminished sleep repose is characteristically observed among gravid women manifesting depressive states.